PENGARUH DAYA SAING, KURS, GDP, DAN HARGA TERHADAP EKSPOR KOPI INDONESIA KE LIMA NEGARA - Sitepu, Marisa Angelia Metami Br; Yudha, I Made Endra Kartika (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 10 (2022): vol.11.10. OKTOBER 2022 [3701 - 4009]DO - 10.24843/EEP.2022.v11.i10.p06, 2022)
The purpose this research analyze competitiveness Indonesian coffee in markets and analyze effect exchange rate, GDP, and international prices on coffee exports to markets of five main countries. Data used 2005-2020 time series in United States, Japan, Malaysia and Egypt and analys with Revealed Comparative Advantage (RCA), and Panel Data Regression processing using eviws-12. Based on the analysis RCA method, Indonesia has comparative advantage with RCA value of > 1, Indonesia has strong competitiveness in the five main export destination countries. On simultaneous testing of variabels analys have a significant effect on Indonesian coffee exports in the five main export destination countries. Partially Competitiveness, GDP, and Prices have a positive and significant effect, while the exchange rate variable has a negative and significant effect on the value of Indonesian coffee exports in the five main destination countries. Keywords: Indonesian Coffee, Exchange Rate, GDP, International Prices, RCA.